Investigation of fouling of thin-film composite (TFC) membranes during wastewater reclamation - Tan, Nicholas Wei Quan (Nanyang Technological University, 2022)
There has been an increase in global freshwater demand as a result of population growth and socio-economic development. This is currently putting a strain on water resources in areas facing water scarcity especially in rural areas. Reverse osmosis (RO) is a key technology which is being used to treat wastewater into reusable water to cope with the rising water demand. However, the membranes used in RO is subjected to different types of fouling processes such as colloidal, organic or biofouling over a prolonged period of time which ultimately hinders the RO membrane’s performance. This leads to a lower RO recovery and water quality in the permeate. In this study, the effect of three groups of factors on RO colloidal fouling such as feedwater composition, membrane properties and hydrodynamic conditions were analysed. It was found that at certain conditions such as higher initial flux, lower pH levels and higher recovery, fouling was more severely affected to a greater extent as compared to others which led to greater reductions in the permeate flux over time. Furthermore, these conditions had an effect on the rejection efficiencies as well. In addition, fouling potentials will be affected by properties of the RO membrane such as surface hydrophilicity or roughness. The data obtained from this study was discussed and found to be consistent with similar trends in previous research studies, thus showing that RO colloidal fouling is indeed a complex problem that can be affected by a multitude of factors.